Liquid state bioconversion of sewage treatment plant sludge in batch fermenter and shake flask - Alam, Md. Zahangir; Fakhru’l-Razi, Ahmadun (Marcel Dekker, 2004)
A study on liquid state bioconversion of sewage treatment plant (STP) sludge was assisted to evaluate the performance of batch fermenter compared to shake flask in a laboratory. Bioconversion of STP sludge was highly influenced by the mixed fungal culture of Penicillium corylophilum and Aspergillus niger after 4 days of treatment. The results showed that about 24.9 g kg-1 dry sludge cake (DSC) was produced with enrichment of fungal biomass protein in fermenter while 20.1 g kg-1 in shake flask after 4 days of fungal treatment. The effective biodegradation of STP sludge was recorded in both fermenter and shake flask experiment compared to control (uninnoculated sample). The results presented in this study revealed that the overall performance of fermenter in terms of sludge cake (biosolids) accumulation and biodegradation of STP sludge was higher than the shake flask.